Integration of Fuzzy AHP and TOPSIS In Decision Support System for Lecturer Academic Promotion - Rakhmi Khalida; khairunnisa Fadhilla Ramdhania (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
Lecturer academic position or known as functional position is a criterion to measure the quality of higher education lecturers. Functional positions are also a form of performance performance for lecturers to be more measurable. Currently, technology is a tool for universities to measure lecturer performance and monitor applications for lecturer functional position increases to avoid the subjective nature that occurs in many cases. This research proposes to integrate the Fuzzy AHP and TOPSIS methods in providing recommendations to universities regarding the order of lecturers who are eligible to apply for functional promotion. This method assesses the relative importance of each criterion (education, teaching, research, community service, and support) and alternative (worthy and not worthy). The results obtained as many as 8 lecturers were declared worthy of promotion recommendations with lecturer 8 and lecturer 7 being the first and second order recommended for eligibility.